Privacy and trust in the Islamic perspective: implication of the digital age - Lubis, Muharman; Kartiwi, Mira (2013)
is slowly degrading the limitation and common understanding of privacy and trust through digital life, which has open world concept. It has become normal procedure when the user must submit their personal details for digital service such as social networking, electronic commerce, personal hosting, etc. Meanwhile, to be able to revealing their privacy willingly, user put their trust on organization to use their data based on agreement. In this sense, user expect their privacy right to be protected securely and actively. The dilemma occurred due to commercialization, consumerism and legislation as interaction issues, which shift the focus of user to identify the importance of their personal data and organization to analyze the process of data management. On the other hand, Islam gave the basic understanding in privacy and trust that emphasize important factor in human determination and intention. This paper will focus on how to define the standard and limitation of the concept privacy and trust based on Islamic perspective in aligning with the implication of digital age related to interest, classification and purpose